Continuities and differences in a Norwegian welfare service context: Comparing conversations about financial and employment problems in 1992 and 2015 (Journal of Comparative Social Work, 2025)
Welfare and social work aim for social justice and self-determination, and the work is sensitive to both its institutional context and to the worker-client relationship. In this article, we re-analyse and compare two sets of collected data (Oltedal, 2000; Olsen, 2022). The data consists of institutional talks between frontline workers and clients in a Norwegian welfare-to-work-service context; the social services (Sosialkontoret) in 1992, and an integrated labour- and welfare service (NAV) in 2015.The institutional framework of the two services shares many similarities, including the overall policy goal of securing people’s financial livelihood, as well as labour market inclusion. We investigate the following question: How is moral and control dealt with in institutional welfare conversations in Norway in both 1992 and 2015, related to clients’ financial and unemployment problems? The aim of the study is to explore changes in institutional talk by identifying and discussing contextual and relational-dependent similarities and differences.The employment control aspect is more visible in 2015 data through social workers’ emphasis on a step-by-step approach wherein measures are reframed, while social workers in 1992 are more inclined to leave it up to clients themselves to make work-life connections. While the financial control aspect is more visible in 1992 through social workers’ emphasis on the client’s moral responsibility, this is less dominant in 2015, in which social workers are acting more neutral and descriptive. The institutional discourse has changed. In 1992, the framing of the talk between frontline workers and client has a stronger moral focus than in 2015. This is due to the animator footing (Goffman, 1981), where workers bring the context and the societal perspectives regarding norms for social welfare recipients into the discussion. In 2015, the principal footing (Goffman, 1981), where the possibility for the frontline worker to voice their own judgement is more visible and the framing of the talk is more relational-dependent.  Changes can also be traced back to differences in welfare policy, where the financial issue is more in focus in 1992, while welfare-to-work is more on the frontline workers agenda in 2015.